Geraldine, The Music Mouse - Leo Lionni (Dragonfly Books, 1979)
While nibbling at a huge hunk of parmesan cheese, Geraldine uncovers a cheese statue of a mouse playing what seems to be a flute but on closer inspection is really its tail. That night Geraldine is woken by silver and gold sounds. (3z(BThis must be music!(3y (Bshe says. And every night the cheese mouse fills Geraldine$1 (Bs hideaway with beautiful music. Then one day her hungry mice friends ask her to share her cheese with them. Geraldine$1 (Bs new love of music infuses her with a magic of her own and provides a satisfying conclusion to this delightful tale.s
Keywords: Team Work, Creativity; Circle Time Book - Relationships / Teamwork /Conflict Resolution -- Circle Time Book - Relationships / Teamwork /Conflict Resolution